Influence of Dietary Fermented Tapioca By-Products on the Performance of Broilers and Ducklings - Wizna; Rizal, Yose; Abbas, Hafil; Dharma, Abdi; Kompiang, I.P. (International Journal of Poultry Science, 2009)
An experiment was conducted to determine the effects of substitution of Bacillus amyloliquefaciens fermented tapioca by-products for some of corn meal in the diets on the performance of broilers and ducklings. 200 unsexed day old broiler chicks and 200 male day old ducklings were randomly allocated into 40 pens (teen chicks or duckling/pen). This experiment was arranged in a completely randomized design with five dietary treatments (0, 10,20, 30 and 40% for broilers and 0, 30, 40, 50 and 60% for ducklings) of fermented by-product tapioca in diets and four replications. Measured variables were those of feed consumption, average body weight gain, feed conversion and carcass percentage. Results of experiment indicated that feed consumption, average body weight gain, feed conversion and carcass percentage were not affected (p>0.05) by levels of Bacillus amyloliquefaciens fermented tapioca by-products in the diets for broilers. However average body weight gain was affected (p<0.05) and feed conversion were highly affected (p<0.01) by levels of Bacillus amyloliquefaciens fermented tapioca by-products in the diets for ducklings. Increasing levels of Bacillus amyloliquefaciens by products of tapioca up to 60% in diets of ducklings increased their body weight gain and reduced their feed conversion. In conclusion, Bacillus amyloliquefaciens- fermented tapioca by-products can be included up to 40% in diets (replace 67% corn meal) for broilers and up to 60% in diets for ducklings (replace 100% corn meal).